Self-powered ZnO/SrCoOx flexible ultraviolet detectors processed at room temperature. (May 2021) - Wang, Dong; Shi, Peng; Xing, Ruofei; Wu, Zhenfa; Wei, Lin; Chen, Yanxue; Ren, Huixue; Yu, Chunfeng; Li, Fangjun
Abstract: Flexible and self-powered ultraviolet (UV) photodetectors can meet the growing demand of next-generation portable, light-weight optoelectronic devices and have attracted increasing attention in recent years. However, it is still challenging to develop self-powered UV detectors with high photosensitivity, fast response time, environment-friendly feature, as well as compatible to flexible substrates. Herein, thin film UV photodetectors based on inorganic ZnO/SrCoOx heterojunction are designed and fabricated on flexible polyimide substrate at room temperature. The built-in electric field between n-type ZnO and p-type SrCoOx films facilitates the separation and transportation of photogenerated carriers without any external bias. A high photosensitivity of (73.8 mA/W) and a quick response time (0.6/4.8 ms) at zero bias are realized under UV light illumination. Moreover, a long-term stability and a good flexibility are also demonstrated. This self-powered flexible UV photodetector fabricated at room temperature is a promising candidate for future energy-efficient, wearable and lightweight optoelectronic devices. Graphical abstract: Unlabelled Image Highlights: Amorphous SrCoOx film, for the first time, is adopted as the p-type semiconductor in optoelectronic devices. Full oxide ZnO/SrCoOx heterojunction was designed and fabricated for self-powered ultraviolet photodetectors. A highest photosensitivity of 73.8 mA/W and a rapid response time of 0.6/4.8 ms were observed in this photodetector. Long-term stability and good flexibility of this self-powered photodetector were demonstrated.